FLANDERS INTERACTION ANALYSIS (FIA) IN ANALYZING TEACHERS-STUDENTS INTERACTION AT THE DIFFERENT EDUCATIONAL LEVEL - Retna Fauziah Adhitya Rini; Misbahudin M.Pd (Journal of English Education Program (JEEP), 2017)
ABSTRACTThis research presents regarding the analysis of flanders interaction in analyzing teachers students interaction in EFL classroom based on 2013 curriculum. This study aimed at describing the kinds as well as analyzing the characteristic of teacher-students interaction in EFL classroom that implements 2013 curriculum. This study employed a qualitative approach, descriptive research design in particular. In analyzing the data, this study was analyzed by means of Flanders Interaction Analysis. Flanders Interaction Analysis is a system that aims to measure the classroom interaction which has 10 ctegories, namely accepting feeling, praising and encouraging, accepting or using ideas of students, asking questions, lecturing, giving directions, criticizing or justifying authority, student-talk response, student-talk initiation and silence (Walsh, 2011). To obtain the data, the researcher conducted classroom observation in two English classess of Peminatan program (Optional program) at the tenth grade in one of Senior High School in Ciamis which implements 2013 curriculum. The findings of this study revealed that the kinds of teacher-students interaction occured in both classes were teacher talk, student talk and silence. Due to teacher talk gained highest percentage in all classroom observation of both teachers, classroom interaction was dominated by teacher talk through emphasizing on asking question. In case of teacher A, from the total of teacher talk (72.29%), teacher A used asking question (27.56%). While in the case of teacher B, from the total of teacher talk (64.93%), teacher B used asking question (25.97%). In term of characteristic of teacher-students interaction, the characteristic in both classes was content-cross Based on the finding above, it could be inferred both teachers used asking questions and lecturing to interact with the students.Key word: Flanders Interaction Analysis (FIA), EFL classroom, 2013 curriculum